Optimization of process parameters for pectin extraction using pomelo (Citrus grandis) peel - Chua, Jubilee Joy V.
Pomelo peels, which contribute large amounts of waste to the environment, is converted into pectin, a naturally derived food additive typically used in the preparation of jams, jellies, and low-pH dairy products. The optimal parameters, extraction time and temperature, were determined using response surface methodology with a central composite design to obtain the highest pectin yield and anhydrouronic acid content. Only the model for pectin yield, however, was able to show significance (p=<0.0001), while anhydrouronic acid content (p=0.4083) showed to be insignificantly affected by the parameter ranges used. The optimal solution generated was determined to be at 90˚C and 120 minutes, and through validation, resulted to a pectin yield of 4.21(0.69)%. Through physico-chemical evaluation, the pomelo pectin was found to produce a highly pure (AUA=73.00(3.71)%) low methoxyl pectin (MeO=2.18(0.30)%; DE=16.88(1.93)%) with low gelling abilities (EW=290.89(13.57) g/eq) but is capable of forming soft, spreadable, and rapid-setting gels. Its inability to solubilize in low temperatures as well as its yellowish color, however, limits pomelo pectin application. For future studies, wider parameter ranges could be used to determine possible factors causing change in the anhydrouronic acid content, and different process combinations may be employed to more efficiently extract pectin from pomelo peels with a higher yield.